Hubungan Antara Indeks Massa Tubuh dan Persen Lemak Tubuh dengan Kebiasaan Makan pada Mahasiswa di Malang: Relationship between Body Mass Index, Body Fat Percentage, and Eating Habits among University Students in Malang - Kusumastuty, Inggita; Maulia, Putri Hersya; Dewi, Diva Regita; Oktania, Rizkyah; Nugroho, Fajar Ari; Handayani, Dian (Amerta Nutrition, 2025)
Background: In 2023, obesity prevalence in Indonesia was reported at 15.7% in men and 31.2% in women. Eating out has become increasingly common among university students in major cities like Malang due to busy schedules, easy access to food accessibility, and lifestyle changes. Objectives: This study aims to examine the relationship between Body Mass Index (BMI), body fat percentage, and eating habits among university students. Methods: This cross-sectional observational study was conducted at Universitas Brawijaya, Malang, involving 385 respondents. The measured variables included BMI, body fat percentage, and eating habits. Eating habits were assessed using a questionnaire covering five indicators: Takeaway food consumption, eating at home, dining at restaurants, consuming supermarket food, and consuming traditional market snacks. Data were analyzed using the Chi-square test and Logistic Regression. Results: Most respondents were female, lived in dormitories or rented housing, and had a family income below five million rupiahs per month. Among the five eating habit indicators, only restaurant dining showed a significant correlation with BMI and body fat percentage (p-value<0.05), while takeaway food consumption, eating at home, consuming supermarket food, and consuming traditional market snacks were not significantly related (p-value>0.05). Conclusions: Eating habits, in general, showed no significant relationship with BMI and body fat percentage, except for restaurant dining, which was significantly correlated with increased body fat percentage.